Biotransferencia de flúor de agua a diferentes tejidos de pejerrey (Odontotesthes bonariensis) - Puntoriero, María Laura (2014)
The presence of fluorine (F), toxic trace element, has relevance in the trophic chain because it can biotrasfer to different levels. It can come from water as food, being chronic ingestion harmful to human beings. Fluorine was found in different water bodies of southwest of Buenos Aires. Chasicó Lake has the highest fluorine concentration. This water body is the most important for commercial and recreational fishing silverside (Odontesthes bonariensis) of the area. The aim of this paper is to analyze the biotransfer of F from water to different silverside tissues in Chasicó Lake. Fish organs were subjected to an alkaline digestion. Fluorine was determined using a fluoride ion selective electrode. F concentrations were 6,4-8,5 mg/L in water and in fish tissues were in gonads: 4,2 to 69,4 μg/g , in liver: 7,1 to 75,3 μg/g , in gills: 49,1 to 110,1 μg/g , in vertebrae: 70,2 to 457,9 μg/g and in muscle: 5,1 to 86,8 μg/g . The concentrations found in muscle were higher than the maximum limit allowable for human consumption, according to CAA (1,5 μg/g). Whereas silverside is a native fish of major commercial importance in Buenos Aires Province, it is important to perform studies on the fluorine concentration to ensure quality for human consumption.